Improving Resident Hand-Off: Implementing a Standardized Electronic Hand-Off System. (October 2015) - Nelson, Marie; Lohr, Rena; Glowacki, Christopher
Abstract : PURPOSE: To improve transitions in patient care by implementing a standardized electronic hand-off system. BACKGROUND: Accurate communication of patient information during transitions of care is vital to the provision of patient care that is safe, effective, and efficient. Before this intervention, methods and processes surrounding transitions in patient care varied widely at our institution. METHODS: Current needs for improving transitions in patient care among residents were assessed. Implementation of a standardized electronic hand-off system across all residency programs within the university system was determined to be the best method to improve patient safety and resident efficiency. All residents in the Creighton University Medical Center system were surveyed to evaluate current practices in transitions in patient care. A standardized electronic hand-off system was then implemented. Eight months later, residents were re-surveyed to evaluate perceptions of how the electronic system affected patient care. All residency and fellowship programs within our institution implemented the electronic hand-off system. Before and after implementation, a group email was sent to all residents and fellows involved requesting voluntary survey participation. RESULTS: Initial survey results revealed a wide variety of hand-off methods in use and more than 50% of residents reported errors of omission occurring greater than once per week. After implementation of the electronic system, 90% of residents felt that errors of omission had either decreased or stayed the same. DISCUSSION: We concluded that implementing the electronic hand-off system for residents improves efficiency and may reduce errors of omission in transitions of care.